Construction and validation of an instrument for the assessment of care provided to people with suicidal behavior - Laura Maria Souza de Linhares; Patrícia Moita Garcia Kawakame; Daniel Henrique Tsuha; Albert Schiaveto de Souza; Ana Rita Barbieri (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To develop and validate an instrument for evaluating primary health care professionals' assistance to people with suicidal behavior. METHODS This was a methodological study, which began with a literature review, followed by the elaboration of an instrument. In its first version, the instrument had 34 items, divided into four domains: "professional characterization," "professional perception " "professional knowledge/abilities," and "organization of the care network." Contents were validated using the Delphi method. Semantic analysis was performed by college-educated primary health care professionals in greater and lesser strata of ability. For internal consistency analysis, Cronbach's alpha coefficient was calculated. The study was conducted between January and December 2017. RESULTS After four Delphi rounds, the instrument was successfully validated. In its final form, it is comprised of 50 items, divided into five domains: "professional characterization," "professional sensibility," "professional experience," "professional knowledge/abilities," and "organization of the care network." Questions belonging to the last four domains have answers on a five-point Likert scale. In the semantic analysis, 93.6% of the evaluations were "good" and "very good." The instrument's general Cronbach alpha was 0.90. CONCLUSIONS The final version of the instrument was able to fulfill its objectives. It is useful as a support for epidemiological research and planning of health actions. The evaluation of professional approaches to suicidal behavior is crucial for the organization of suicide assistance services in primary health care, and for the integration of services provided by different care units.